2002
DOI: 10.1016/s1569-1993(02)00095-4
|View full text |Cite
|
Sign up to set email alerts
|

Nebulised dornase alpha: adherence in adults with cystic fibrosis

Abstract: There is variability in adherence to dornase alpha in adults with CF and patient self-reporting is likely to over-estimate drug collection from the pharmacy. Further study of the long-term effects of dornase alpha is required. To date, proven interventions to enhance adherence are limited and require investigation in CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 13 publications
2
27
0
Order By: Relevance
“…15 Even when dornase alfa is demonstrated to improve lung function in an individual, adherence to therapy is often less than the physician presumes. 7 Consequently, the demonstration in this study of equal utility of dornase alfa before or after physiotherapy provides the first evidence for the clinician to advocate more flexibility with this therapy in relation to physiotherapy, which …”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…15 Even when dornase alfa is demonstrated to improve lung function in an individual, adherence to therapy is often less than the physician presumes. 7 Consequently, the demonstration in this study of equal utility of dornase alfa before or after physiotherapy provides the first evidence for the clinician to advocate more flexibility with this therapy in relation to physiotherapy, which …”
Section: Discussionmentioning
confidence: 71%
“…7,16 In addition, the individual response of a patient to a therapeutic trial of dornase alfa may differ when used before or after physiotherapy as shown in this study. Although a standardized trial of dornase alfa is considered to be 4 weeks, previous work has shown that a therapeutic response can be seen within 2 weeks and dissipate within 2 weeks.…”
Section: E552mentioning
confidence: 91%
See 1 more Smart Citation
“…3,10,11,20,[22][23][24][25][27][28][29][31][32][33][34][35][36][37][38][39] Eighteen papers were of low quality, and 2 were of moderate quality. The categories of medications are summarized below (Table 3).…”
Section: Medicationmentioning
confidence: 99%
“…A number of strategies were used to determine adherence. Two studies used pharmacy refill data, 35,36 3 used participant questionnaires, 3,25,31 2 used parent questionnaires, 3,31 one used participant interviews, 36 one used a collection of empty medication vials, 11 and one used daily telephone diaries. 3 Mean adherence ranged from 54% by participant interview 36 to 77.8 Ϯ 44.1% by patient questionnaire.…”
Section: Medicationmentioning
confidence: 99%